Enrichment of Environmental Sustainable Development, Green Finance, and Economic Complexity for Reduction of Ecological Footprints - Yen, Nguyen Hong; Huyen, Nguyen Thi Thanh (International Journal of Energy Economics and Policy, 2025)
Green finance is anticipated to play a crucial role in balancing environmental sustainability with economic growth, enabling the growth of several industries. Using data from 41 countries between 2004 and 2022 and a Panel Vector Autoregressive (PVAR), the analysis shows that the impact of green finance and CO2 on economic complexity was positive in the whole period, while the reverse relationships were negative in the whole period. Meanwhile, green finance positively impacts CO2 in the whole period, and vice versa. This emphasizes the need for stronger, more thoughtfully crafted regulations that strike a balance between sustainability and economic expansion.